Modeling and Performance Testing of Anti-Lock Braking System (ABS) with Variation of Road Friction Coefficient to Braking Distance - Ulum, Miftahul; Arifianto Patriawan, Desmas (Universitas Trunojoyo Madura, 2022)
Automated vehicles are increasingly being researched and developed to reduce accident rates. The braking system is an integral part of the safety factor in the vehicle. One of the development systems in braking on vehicles is the Anti-lock Braking System (ABS). ABS is a vehicle b that prevents the wheels from locking during sudden braking. The research was conducted by modelling and designing the ABS braking system using SIMULINK software on MATLAB. This research was conducted by varying the coefficient of braking friction on dry asphalt, wet asphalt, dry soil, and wet soil by paying attention to the braking distance. In the first test, the first test of the non-ABS system sets 0.9. The results were obtained with the shortest braking distance of 20 meters and the farthest, 34.5 meters. As for the results with ABS, the shortest braking distance is 17.95 meters, and the farthest is 27 meters. From the analysis that has been done, it is found that the ABS is better than the non-ABS system. This is because ABS regulates the braking calliper and is adjusted to the vehicle’s dynamics instead of statically. When there is a difference in vehicle speed with different wheels too far (while the wheels will lock), the calliper on the brakes will open and close dynamically, unlike non-ABS